Hemolytic Uremic Syndrome; Report of a Case With late Recovery Of Renal Function - M. Akhavan Sepahi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2008)
Background and ObjectiveHemolytic uremic syndrome (HUS) is characterized by triad of microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure. It is more common in children younger than the age of 4 years and is the most common cause of acute renal failure in many parts of the world in this range of age. The classic form of the disease occurs after an episode of acute diarrhea which may lead to chronic renal failure in 9% of cases. Here in we report a case of HUS with recovery of renal function after 15 months of dialysis. Case report A 12 year old boy was admitted with major clinical symptoms including acute bloody diarrhea, followed by acute renal failure, thrombocytopenia and severe microangiopathic hemolytic anemia. Peripheral blood smear showed probability of HUS. Peritoneal dialysis was started and later followed by hemodialysis. Eventually after 15 months of dialysis he obtained normal renal function and now after 3 years he is in good health with normal renal function.Conclusion: Recovery of renal function in HUS is possible even after a prolonged period of renal failure.Keywords: Hemolytic-uremic syndrome, Children, Child, Late recovery.